CITRA WANITA DALAM NOVEL CINTA SUCI ZAHRANA KARYA HABIBURRAHMAN EL SHIRAZY - Sifa, Nurul Hidayah Laylatul; Areza, Rhezina Juni; Sudiatmi, Titik (Jurnal Bahasa Indonesia Prima (BIP), 2023)
Writing entitled "The Image of Women in the Novel Cinta Suci Zahrana by Habiburrahman El Shirazy" which has the aim of explaining the image of women in the novel "Cinta Suci Zahrana" by Habiburrahman El Shirazy. This research method is descriptive qualitative. Research data in the form of words, phrases, and sentences derived from the novel "Cinta Suci Zahrana" by Habiburrahman El Shirazy. The results of this research analysis: (1) The image of a woman as an individual, (2) The image of a woman as a wife, (3) The image of a woman as part of society. The results of the analysis of women's images examine the image of women in character Zahrana in the novel Cinta Suci Zahrana by Habiburrahman El Shirazy. Zahrana is the main character in the novel Cinta Suci Zahrana by Habiburrahman El Shirazy. At this time, the image of women can already be equal to that of men. Women have the power to support their progress and achievements as career women.